The Effects of the Computer-Based Program, "Career Search," on the Vocational Maturity of Grade Nine Students - Drodge, E. N.; Sumarah, J. C. (Canadian Journal of Counselling and Psychotherapy, 2011)
This study investigated the effects of a computer-based career guidance program, "Career Search," on the vocational maturity of grade nine students. A pretest sample of 31 male and 26 female 14-year-olds completed the Career Development Inventory School Form. Each student in an experimental group of 27 students then completed Holland's Self-Directed Search, finding a three-letter code that was used in the Career Search program. Students spent one class period using the computer in order to identify occupations matching Holland's code. The remaining students, comprising the control group, did not complete the Self-Directed Search or the (Career Search. Two weeks following the pretest, both groups again completed the Career Development Inventory as a posttest. The results show no statistically significant difference between the posttest control and experimental groups at the .05 a priori level of significance. The results do suggest, however, that school counsellors can be cautiously optimistic about the Career Search program.